Low-Cost Linearity Range Enhancement for Linear Variable Differential Transformer - Prommee, Pipat; Angkeaw, Krit; Karawanich, Khunanon (My University, 2022)
This research proposes a low-cost and low-complexity technique to enhance the linearity range of linear variable differential transformer (LVDT) using logarithmic approximation and summing/subtracting operation. The proposed technique utilizes the feedforward approach and thus encounters no divide-by-zero behavior from inverse functions. The nonlinearity of LVDT can be counteracted by simply manipulating the parameters of the canceller circuit. Besides, the proposed technique can be applied to various LVDT nonlinearity types. The proposed linear enhancing circuit consists of operational amplifiers and a small number of passive elements. The nonlinearity cancellation could be further enhanced using a temperature-compensation circuit. Simulations were carried out using two different LVDT nonlinearity types: LVDT#1 and #2. The simulation results showed that the linearity enhancing circuit effectively enhances the LVDT linearity range, with the linearity errors of 0.51% and 1.83%, respectively. To validate, experiments were undertaken with the identical LVDT nonlinearity types using a circuit prototype, and the measured linearity errors are around 2.5% and 5.5%, respectively. The simulation and experimental results are agreeable with the theory, indicating that the proposed technique enhances the linearity range.
Keywords: approximation; Linearity; low-cost; LVDT; position sensor; temperature independence